Studi Empiris tentang Dampak Ketidakamanan Pekerjaan terhadap Niat Pindah Kerja di Kalangan Akuntan Pendidik di Perguruan Tinggi Indonesia - Agus, Roni (Jurnal Rumpun Ilmu Ekonomi, 2023)
The purpose of this study was to re-examine the effect of the antecedent job insecurity variable on turnover intentions, using Ashford's (1989) research model approach and Ameen et al.'s (1995) questionnaire instrument. The data were collected from 247 (24.7%) academic accountants from universities in Indonesia through mail questionnaires. The data was analyzed using the multivariate technique of Structural Equation Model (SEM) with the programs AMOS and SPSS. The study's results supported the hypothesis that role conflict, locus of control, and organizational change had an effect on job insecurity. However, role ambiguity failed to show a significant effect on job insecurity. The study also found a direct effect of job insecurity on turnover intentions. The study found that an individual's perception and personality can lead to negative effects on job insecurity and turnover intentions simultaneously. It also suggests that academic accountants who feel insecure about their profession have a great chance to explore alternative job opportunities.